Modified Mediterranean diet v. traditional Iranian diet: efficacy of dietary interventions on dietary inflammatory index score, fatigue severity and disability in multiple sclerosis patients. Issue 7 (14th October 2022) - Bohlouli, Jalal; Namjoo, Iman; Borzoo-Isfahani, Mohammad; Poorbaferani, Fariborz; Moravejolahkami, Amir Reza; Clark, Cain C. T.; Hojjati Kermani, Mohammad Ali
Abstract: Background: Current evidence suggests that adherence to the Mediterranean diet (MeD) can reduce inflammation in chronic diseases; however, studies pertaining to relapsing-remitting multiple sclerosis (RRMS) are limited. Therefore, the aim of this study was to investigate the potential of the modiﬁed MeD (mMeD) in improving Dietary Inflammatory Index (DII) scores, disability and fatigue severity, compared with traditional Iranian diet (TID), in RRMS patients. Results: Of the 180 patients enrolled, 147 participants were included in the ﬁnal analysis (n of mMeD = 68; n of TID = 79). Self-reported adherence was good (˜81 %). Dietary intakes of forty-five food parameters were assessed through the FFQ. The mMeD significantly reduced DII scores after 6 months (2·38 ± 0·21 to −1·87 ± 0·86, P < 0·001), but TID did not elicit any changes (2·21 ± 0·44 to 2·14 ± 1·01, P = 0·771). Additionally, Modified Fatigue Impact Scale (MFIS) total score decreased significantly (72·4 ± 17·2 to 63·9 ± 14·2, P < 0·001), whereas there was no considerable improvement for Expanded Disability Status Scale (EDSS) in the mMeD group. Methods: After initial screening ( n 261), 180 RRMS patients were randomised to receive mMeD or TID (as control) for 6 months. DII score, EDSS and twenty-one-item MFIS were evaluated at baseline and trial cessation. Multivariate ANCOVA was conducted and adjusted for age, gender, body weight, BMI, education level, supplement use, family history and duration of MS. Conclusion: Adherence to mMeD, for 6 months, improved dietary inflammatory status and fatigue severity in RRMS patients; however, the TID did not positively impact dietary inflammation and MFIS score.